2019
DOI: 10.3390/medicina55120762
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic and Non-Pharmacologic Interventions for HIV-Neuropathy Pain. A Systematic Review and a Meta-Analysis

Abstract: Background and Objectives: Among HIV infection symptoms, sensory neuropathy (HIV-SN) remains a main cause of suffering, with incidence varying from 13–50%. So far, numerous pharmacological and non-pharmacological treatments have been tested, although few evidence-based analgesic options are available. We conducted an up-to-date systematic review and meta-analysis of the literature in order to evaluate the efficacy and safety of pharmacologic and non-pharmacologic treatments for pain control, in patients with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 59 publications
(327 reference statements)
0
10
0
1
Order By: Relevance
“…Folate is easily conjugated to various nanomaterials and several high receptor expressing cancer cell lines exist for testing these nanoconjugates [72]. The field of nanomedicine, in general, also experienced rapid citation growth during this time frame [80]. An analysis of citation rates per time, Table 2, revealed that the top two citations by Kam et al, and Liong et al, were tied with 119 citations per number of years since publication.…”
Section: Discussionmentioning
confidence: 99%
“…Folate is easily conjugated to various nanomaterials and several high receptor expressing cancer cell lines exist for testing these nanoconjugates [72]. The field of nanomedicine, in general, also experienced rapid citation growth during this time frame [80]. An analysis of citation rates per time, Table 2, revealed that the top two citations by Kam et al, and Liong et al, were tied with 119 citations per number of years since publication.…”
Section: Discussionmentioning
confidence: 99%
“…Quanto à acupuntura no controle da dor induzida por quimioterapia, por mais que os estudos analisados apontem melhora significativa e benefícios adicionais, como redução de estresse e qualidade de sono, tais evidências são de muito baixo nível. (Li et al, 2019) (Amaniti et al, 2019).…”
Section: Medicamentos Indutores De Dor Neuropáticaunclassified
“…72 The eld of nanomedicine, in general, also experienced rapid citation growth during this time frame. 80 An analysis of citation rates per time, Table 2 an average citation rate of 103. Assessing the citation rate over time adds another layer of depth to the study of citations.…”
Section: Co-author Bibliometric Networkmentioning
confidence: 99%